ANALYSIS OF SEVERE STORM AND HIS IMPACT ON 3 AND 4 DAYS OF NOVEMBER OF THE 2007 IN THE SAO PAULO STATE – BRAZIL - Martorano-Suarez-Pardo, Natália (2013)
Currently, research on severe storms and their impacts are relevant because they alter the spatial organization. These atmospheric phenomena are difficult to predict, because to know its origin, it is necessary the combination of various meteorological parameters that induce a potentially devastating system. Thus, the aim of this study was to identify the weather systems that worked in the São Paulo State - BRA and identify the environmental impacts on episode of severe storm.